Physical and chemical properties at high temperatures of a polypropylene and steel fiber highstrength concrete - Caetano, Hugo (2019)
Concrete is a heterogeneous material compounded of aggregates embedded in a cement paste matrix. The heterogeneity of concrete constituents can result in severe thermal damage at the cement pasteaggregate interface. When cement paste is exposed to high temperatures, different hydration products gradually lose water causing mass loss. This paper presents the results of an experimental investigation on the physical and chemical properties of a steel and polypropylene fibre high strength concretes at elevated temperatures. Several tests were carried out, such as thermal analysis (TGADTA), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Five concrete compositions with different steel fibres dosages and types were selected for the study: one without steel fibres, two with DRAMIX 3D steel fibres and two with DRAMIX 5D steel fibres (both with 45 and 75 kg/m3). All compositions had the same amount of polypropylene fibres (2 kg/m3). The temperatures levels tested were: 20, 200, 500, 800 and 1000 °C. These tests were performed with the purpose of evaluating the temperature effect on mineralogical changes that occurred in the hardened cement paste and its influence on compressive strength of these concretes at high temperatures.